The influence of Bruner's theory in mathematics on the learning outcomes of students in grade IV SD IT Samawi - Syafriza, Azizatul Alif (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
Bruner's theory focuses on students' cognitive abilities in determining success. The purpose of the research using Bruner's learning theory is to determine the improvement of student learning outcomes in mathematics learning. The three stages of learning contained in Bruner's theory are enactive, iconic and symbolic. This research uses pre-experimental designs with a One-Group Pretest-posttest research design. SDIT Samawi as a research site with the subject of class IV Al-Ghozali, totalling 27 students. The results of the study using Bruner's theory, the pretest was 55.19 while the posttest was higher on average at 80.74. The results of data analysis of Shapiro-Wilk normality test pretest of 0.14 > 0.05 and posttest of 0.35 > 0.05 which means normal distribution. T-test of 0.00 <0.05 which means HO is rejected and Ha is accepted. This means that there is a significant influence between the resulst of the pretes and posttest using Bruner’s learning theory in learning mathematics for grace IV students of SDIT Samawi. The use of theory in learning can increase student activity in learning.